Upregulation of cholesterol metabolism as a hallmark of midbrain neurodegeneration induced by iron overload - Maniscalchi, Athina (2023)
Iron (Fe) accumulation in specific brain areas and ferroptosis are associated with various neurodegenerative disorders. We have previously established an in vivo model of Fe overload (C57BL/6 mice treated with Fe 333 mg/kg) with midbrain neurodegeneration and lipid cacostasis. Our aim was to study the link between lipid metabolism alterations and ferroptosis taking into account neuroglial metabolism. In midbrain of Fe-overloaded animals, we detected a decrease in the expression of SLC7A11 and an increase in ACSL4 (p<0.001), both markers of ferroptosis. We found that cholesterol (chol) was elevated in midbrain of Fe-treated mice, coincidentally with SREBP2 and ABCA1 upregulation (p<0.001). In addition, increased levels of CPT1c (p<0.001) were observed after Fe overload, indicating an enhanced β-oxidation for the removal of fatty acid released by lipolysis. In the open field test, Fe-overloaded mice displayed motor impairment, with a lower rearing activity, a shorter time spent in the central square, and a longer time in the periphery (p<0.001). Next, we investigated chol metabolism in dopaminergic neurons and astrocytes exposed to Fe overload with ferric citrate ammonium (FAC). Chol content in neurons (N27), astrocytes (C6), and mouse primary glial culture was increased both in intracellular compartments as well as in secretomes after Fe treatment (p<0.001). This rise correlated with an increase in chol de novo synthesis and transport, respectively, by means of HMGCR and ABCA1 upregulation (p<0.001). To study the link between chol accumulation and ferroptosis, cells were exposed to the inhibitor ferrostatin (FER). We found that FER reduced chol levels when cells were exposed to FAC (p<0.001). Our findings indicate that altered chol metabolism could be a biomarker of midbrain neurodegeneration triggered by ferroptosis, with motor impairment as a final outcome